2011
DOI: 10.1159/000323753
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pseudomembranous Colitis Four Months after Initiation of Rifampicin

Abstract: Pseudomembranous colitis (PMC) may develop with long-term antibiotic administration, but is rarely reported to be caused by antitubercular agents. We present a case of PMC that occurred 120 days after starting rifampicin. A 74-year-old man was diagnosed with pulmonary tuberculosis and started on a standard HERZ regimen (isoniazid, ethambutol, rifampicin, pyrazinamide). After 4 months of HERZ, he presented with frequent bloody, mucoid, jelly-like diarrhea and lower abdominal pain. Sigmoidoscopy revealed multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The emergence of rifampicin-resistant C . difficile has been reported in patients with prolonged rifampicin use [19]. In our study, all PCR ribotype 046 strains isolated from patients with prolonged rifampicin therapy were highly resistant to this drug.…”
Section: Discussionsupporting
confidence: 49%
“…The emergence of rifampicin-resistant C . difficile has been reported in patients with prolonged rifampicin use [19]. In our study, all PCR ribotype 046 strains isolated from patients with prolonged rifampicin therapy were highly resistant to this drug.…”
Section: Discussionsupporting
confidence: 49%
“…Rifampicin was previously shown to induce CDI in patients receiving anti-tuberculosis treatment [44]. Additionally, prolonged use of rifampicin has resulted in high resistance rates in some settings, consequently promoting the persistence of resistant C. difficile strains in patients undergoing tuberculosis treatment [45,46]. In support of this, we previously reported that a large proportion of C. difficile strains isolated from the same study population showed resistance to rifampicin [9].…”
Section: Discussionmentioning
confidence: 61%
“…Previously, prolonged rifampicin use, especially in the treatment of TB, was implicated in the emergence of rifampicin resistance in C. difficile ( Choi et al., 2011 ). Kenya is listed by the World Health Organization (WHO) as one of the 30 high burden TB countries ( Enos et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%